In Vivo Cross-Sectional Observation and Thickness Measurement of Bulbar Conjunctiva Using Optical Coherence Tomography - Zhang, Xingru; Li, Qingsong; Liu, Bing; Zhou, Huanming; Wang, Hanming; Zhang, Zhengyong; Xiang, Minghong; Han, Zhumei; Zou, Haidong (Investigative ophthalmology & visual science, 2011)
To observe in vivo bulbar conjunctival structures, and determine the reproducibility of thickness measurements of normal human conjunctiva through optical coherence tomography (OCT) images. The bulbar conjunctivas of three study groups were observed: five enucleated porcine eyes with 20 um thickness aluminum foils inserted beneath conjunctival stroma; five glaucoma patients with 6-0 thread placed beneath conjunctival stroma during trabeculectomy; and 18 normal subjects. The cross-sectional conjunctival images were acquired using the scanning protocol from an optical coherence tomography device (Anterior Segment 5 Line Raster scanning protocol, Cirrus HD-OCT; Carl Zeiss Meditec, Inc., Dublin, CA). The thickness of different conjunctival layers was measured using central corneal thickness measurement software in the 18 normal subjects. Two reproducible parameters-interobserver (within-subject between-examiners) and intraobserver (within-subject between-date)-were estimated with intraclass correlation coefficients (ICC). A thin hyporeflective surface layer, corresponding to the conjunctival epithelium layer, was observed. Beneath it, the conjunctival stroma appeared hyperreflective and was separated by a demarcation from the underlying progressively lower reflective Tenon's capsule. The anatomic location of the demarcation, which represents the loose connection between the conjunctival stroma and Tenon's capsule, was confirmed by inserting aluminum foil in porcine eyes, and by a 6-0 thread mark in glaucoma patients' eyes. The average conjunctival epithelium, stroma, and full thickness of the 18 normal subjects was 47.3 ± 8.4 um, 190.8 ± 47.5 um, and 238.8 ± 51.1 um, respectively. The intraobserver and interobserver intraclass correlation coefficients ranged from 0.918 to 0.985. It is possible to accurately image and measure the cross-sectional structures of the bulbar conjunctival tissue with high resolution OCT.